2016
DOI: 10.1186/s12906-016-1048-6
|View full text |Cite
|
Sign up to set email alerts
|

Passiflora incarnata attenuation of neuropathic allodynia and vulvodynia apropos GABA-ergic and opioidergic antinociceptive and behavioural mechanisms

Abstract: Background: Passiflora incarnata is widely used as an anxiolytic and sedative due to its putative GABAergic properties. Passiflora incarnata L. methanolic extract (PI-ME) was evaluated in an animal model of streptozotocininduced diabetic neuropathic allodynia and vulvodynia in rats along with antinociceptive, anxiolytic and sedative activities in mice in order to examine possible underlying mechanisms. Methods: PI-ME was tested preliminary for qualitative phytochemical analysis and then quantitatively by proxi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
30
0
8

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(42 citation statements)
references
References 116 publications
0
30
0
8
Order By: Relevance
“…A second study (Sampath, Holbik, Krenn, & Butterweck, ) used differential EPM performances in male C57BL/6 J mice to ascertain optimal fractionalisation methods, and a third (Wolfman, Viola, Paladini, Dajas, & Medina, ) used anxiolytic and sedative paradigms (EPM, hole board and horizontal wire) in male CF1 mice to examine the constituent chrysin (5,7‐dihydroxyflavone) with a diazepam comparator, reporting no significant differences in anxiolytic effect, but an increase to head‐dipping and myo‐relaxant properties via horizontal wire test in the BDZ group. Finally, a recent study (Aman et al, ) observed anxiolytic and sedative effects of P. incarnata in staircase and open field tests, with BALB/c mice and female Sprague Dawley rats, which were antagonised by pentylenetetrazole, indicating the behavioural effects of P. incarnata occurred through GABA‐ergic mechanisms; however, precise mechanisms were again unclear.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A second study (Sampath, Holbik, Krenn, & Butterweck, ) used differential EPM performances in male C57BL/6 J mice to ascertain optimal fractionalisation methods, and a third (Wolfman, Viola, Paladini, Dajas, & Medina, ) used anxiolytic and sedative paradigms (EPM, hole board and horizontal wire) in male CF1 mice to examine the constituent chrysin (5,7‐dihydroxyflavone) with a diazepam comparator, reporting no significant differences in anxiolytic effect, but an increase to head‐dipping and myo‐relaxant properties via horizontal wire test in the BDZ group. Finally, a recent study (Aman et al, ) observed anxiolytic and sedative effects of P. incarnata in staircase and open field tests, with BALB/c mice and female Sprague Dawley rats, which were antagonised by pentylenetetrazole, indicating the behavioural effects of P. incarnata occurred through GABA‐ergic mechanisms; however, precise mechanisms were again unclear.…”
Section: Resultsmentioning
confidence: 99%
“…Aman et al (); Dhawan et al (); Elsas et al (); Grundmann et al (); Sampath et al (), Wolfman et al ()…”
Section: Resultsunclassified
“…In addition, ethyl 9-hexadecenoate was detected just in seeds too. On the contrary, it has been detected in aerial parts of Passiflora incarnate L. methanolic extract (Aman et al, 2016).…”
Section: Resultsmentioning
confidence: 91%
“…However, it is plausible that binding to the GABA‐site of the GABA A receptor is one mode of action of the plant extract (Appel et al, ). Evaluating the attenuation effects of P. incarnata in neuropathic allodynia and vulvodynia, it was suggested that the methanolic extract of the plant possesses peripheral and central phasic as well as tonic anti‐nociceptive activity, mediated through modulation of GABA A and opioid receptors (Aman et al, ).…”
Section: Discussionmentioning
confidence: 99%